Improving Range of Motion through Leg Extension Exercise and Static Bike Exercise for Osteoarthritis Genu - I.A. Pascha Paramurthi; Komang Tri Adi Suparwati; I Made Dhita Prianthara; I Wayan Aris Yuliana (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Aging is identical with decreased functional abilities, such as prolonged standing, walking, squatting, running, or other activities. These decreases in functional ability can be caused by a degenerative disease, namely osteoarthritis (OA) genu resulting in a limited motion in the knee joint caused by a decrease in range of motion. Treatments for OA Genu cases include leg extension exercise and static bike exercise to maintain and to increase the range of motion (ROM) of knee joints.  This study was a Quasi Experimental study. The study lasted for five weeks from May-June. The sample of this study were 24 people. The results of the study found that the ability to movement extension and knee flexion in both groups increased. Both groups obtained p  value = 0.625 for extension and p value = 0.062 for flexion.  The p value of extension and flexion is p0.05. Results showed that, after the intervention in both groups, the osteoarthritis  patients at Siloam Hospitals Bali had improved flexion ROM and knee extension. Based on the difference value before and after treatment, the percentage increase in range of motion extension and flexion in the static bike group was slightly higher than the leg extension exercise group. It concludes that leg extension exercise and static bike exercise are equally good in increasing ROM of osteoarthritis patients. Leg extension exercises and static bike exercise can be used as alternative exercises to improve the ability to bend and to straighten knee joints experiencing limitations or stiffness.